High-rate mechano-stimulation alters proliferation- and maturation-related signaling of oligodendrocyte precursor cells in a 3D hydrogel - Ryosuke Yokosawa; Rachel A. Mazur; Kelsey A. Wilson; Jacob H. Lee; Noah W. Showalter; Kyle J. Lampe; Pamela J. VandeVord (Mechanobiology in Medicine)
Traumatic brain injury (TBI) leads to neuroinflammation and is associated with chronic neurodegeneration. Many TBI studies aim to understand further the mechanism by which cells in the brain respond to the mechanical forces associated with TBI. In particular, mild TBI is the most common level of injury among TBI patients, and the reactivity of glial cells is a key mechanism in understanding mild TBI. However, there is a lack of studies focusing on oligodendrocyte precursor cells (OPCs). OPCs respond to the injury by migration, proliferation, and differentiation into oligodendrocytes (OL) to assist in post-injury repair. Given their ability to proliferate and differentiate, OPCs are a promising therapeutic target for OL regeneration. Despite their important role in maintaining normal neuronal functions, the response of OPCs to mechanical insult remains poorly understood. Thus, this study aims to elucidate the cellular responses of OPCs using a brain-tissue mimicking in vitro 3D hydrogel platform to identify key signaling pathways driving their response. In this study, we applied a high-rate pressure wave to OPCs to induce mild TBI and assess subsequent cellular and molecular responses by quantifying cell growth, metabolic activity, and gene and protein expression. Although the high-rate mechanical insult did not significantly impact cell survival, it induced transcriptomic and proteomic changes in molecular targets related to OPC proliferation and maturation, including PDGFRA, GALC, CTNNB1, and HSP90AB. These dysregulations and altered molecular profiles provide valuable insights into the OPC injury response and may serve as potential therapeutic targets for treating neurodegeneration.